MENGEMBANGKAN KEMAMPUAN SEKRETARIS DALAM BIDANG PEMASARAN - Sofyan Mufti Prasetiyo; Muhammad Toriq Alfasyah; ALDI GIOVANI; Kenang Alam Firdaus (CV. Multi Kreasi Media, 2022)
− A secretary today is not only required to know administrative and clerical work. A secretary who has more responsibility in the field of marketing has added value for the company and for himself. The thing that a secretary has to do to be able to perform the role of a secretary and a marketing person is to broaden her knowledge in any field for the betterment of the company, especially in the field of marketing. If the two roles, functions and duties of these two professions are combined properly and professionally, it will strengthen the success of a company and become a driving force for the progress of a company or organization. The success of a company is a target that must be achieved by a marketing secretary. To develop a marketing strategy, the main factors that must be carried out by a secretary are building self-confidence, taking positive or negative views from the marketing side, implementing goals, then developing marketing tactics, budgeting and controlling them.